RAMSAY HUNT SYNDROME: A CASE REPORT - Gavrila, Priska Gian; Rizaldy Taslim Pinzon (Acta Neurologica Indonesia, 2025)
Introduction : Ramsay Hunt Syndrome or Herpes Zoster Oticus, is a rare and severe complication of varicella zoster virus reactivation. The syndrome consists of: the presence of vesicles in the auditory canal, otalgia, and ipsilateral facial paralysis. If this condition was not treated properly, the full recovery chances only occurs in as little at 20% of cases. Early treatment with steroid and antiviral that started within 72 hours will improve the prognosis. We report a rare case of Ramsay Hunt Syndrome that occurs after 20 days of rash eruption. Case Report : We report a case of 56-year-old male that referred because of painful herpetic neuralgia and facial nerve palsy. The patient developed right-sided facial burning pain that followed with the presence of erythematous, vesicular rash erupted at fore head and ear. Exam showed a similar rash along the auricle and the external auditory canal. On day 24, the patient woke up with partial right-sided facial paralysis and he was referred to the neurology clinic. In the neurology clinic, Ramsay Hunt Syndrome was diagnosed. Discussion : We report a rare case of Ramsay Hunt Syndrome. The mechanism involve reactivation of dormant varicella zoster virus. After primary varicella infection, the virus may stay dormant in sensory dorsal root ganglia. The reactivation causes shingles, ipsilateral vesicular eruption that limited with dermatomal distribution. Conclusion : We report a rare case of Ramsay Hunt Syndrome. This was a very rare complications of varicella zoster reactivation. Keywords: Neuralgia1; Facial Palsy2; Ramsay Hunt3 ; Varicella Zoster4